Investigating the role of gut microbiome in the association between ambient air pollution and type-2 diabetes mellitus: a causal inference approach using review of evidence to date - Mandal, Siddhartha; Kuriakose, Steena; Shridhar, Krithiga (Frontiers in Environmental Health, 2024)
Pollutants in ambient air have been linked with type-2 diabetes mellitus (T2DM) in low as well as high pollution scenarios. Mechanisms of action include disruption of endothelial function, imbalance in the autonomic nervous system and direct translocation. Although reductions in exposure to ambient air pollution (AP) could translate to meaningful clinical and public health benefits, policy changes targeting AP are usually at the population level, multisectoral, and time consuming. The human gut microbiome (GM) is an ecosystem within individuals which has been linked with health in both beneficial and detrimental ways. During the last decade, mechanistic and epidemiological research on GM suggests altered microbial diversity and differential composition influencing T2DM through inflammation, metabolites, and microbial functions. This offers a scope to design individual level interventions to target AP related T2DM through GM. In this paper, we presented a combination approach of evidence synthesis by literature review and application of causal inference framework to investigate the role of GM in the association of AP and T2DM, to help design epidemiological studies and direct data analysis. We formulated Directed Acyclic Graphs with methodological considerations for mediatory, interacting, or effect modification role of GM in the association of AP and T2DM. Additionally, we considered the emerging links between gut and oral microbiome, the different T2DM disease patterns in South Asia, and unique coexposures in these settings (for example, indoor air pollution).